'We'll show you gang': The subterranean structuration of gang life in London. (February 2015) - Densley, James A; Stevens, Alex
This article uses data from interviews with 69 self-described members and associates of street gangs in London to explore how young people choose their actions and construct their identities from the material and cultural resources they find in their locales. It explores 'drift' as a potential explanation of actions of gang members and finds it wanting. It suggests that Giddens' concept of structuration, when combined with Matza and Sykes' notion of subterranean traditions, offers a powerful tool for the explanation of how and why some young people in socio-economically deprived urban areas seek association with gangs through the performance of violence.